EP591 Survival and recurrence rates in stage II endometrial cancers in related to uterine-risk stratification after the introduction of lymph node resection and the omission of postoperative radiotherapy. A danish gynecological cancer study group. (1st November 2019) - Ørtoft, G; Høgdall, C; Hansen, ES; Dueholm, M
Abstract : Introduction/Background: To evaluate the survivals and recurrences in relation to uterine-risk stratification after the introduction of lymph node resection and omission of postoperative radiotherapy in stage II endometrial cancers. Methodology: This national cohort study includes all 708 cases with cervical stromal invasion of 4380 radically operated endometrial carcinomas (2005–2012). Five-year Kaplan-Meier survival estimates and actuarial recurrence rates were calculated. Results: Of 708 cases with cervical stromal invasion 461 were finale stage II. The strongest predictor for survival and recurrences in final stage II cases was myometrial invasion, tumor grade and type e.g uterine risk factors (low-, intermediate- and high-risk) with a very good prognosis for stage II cases with otherwise low-risk (grade 1 or 2 and <50% myometriel invasion and cervical stromal invasion), almost comparable to that of low-risk stage I, whereas cervical stromal invasion in intermediate and high-risk cases significantly increased the risk of recurrences and decreased cancer-specific survivals compared to corresponding stage I cases (figure 1). Lymph node resection in 355 cases with cervical stromal invasion diagnosed 27.9% with lymph node metastasis and upstaged 18.1% from stage II to IIIc, resulting in higher survivals and lower recurrences in lymph node resected as compared to non-lymph node resected. Radical as compared to simple hysterectomy did not alter survivals. Stage II (117 cases) treated with external beam radiotherapy had significant lower local recurrence rates, but unchanged survivals compared to non-irradiated. Conclusion: Uterine risk groups (low-, intermediate- and high-risk) are the strongest predictor for survival and recurrence and should be considered when advising adjuvant therapy for endometrial cancer stage II. Lymph node resected stage II had increased survivals and decreased recurrences. Omitting radiotherapy increased local vaginal recurrences without affecting survivals. Disclosure: Nothing to disclose.